2012
DOI: 10.1007/s10162-012-0360-1
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Tuning of the Cervical Vestibular-Evoked Myogenic Potential (cVEMP) Recorded from Multiple Sites along the Sternocleidomastoid Muscle in Normal Human Subjects

Abstract: Frequency tuning of tone burst-evoked myogenic potentials recorded from the sternocleidomastoid muscle (cervical VEMP or cVEMP) is used clinically to assess vestibular function. Understanding the characteristics of cVEMP is important for improving the specificity of cVEMP testing in diagnosing vestibular deficits. In the present study, we analyzed the frequency tuning properties of the cVEMPs by constructing detailed tuning curves and examining their morphology and dependence on SCM tonic level, sound intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 47 publications
2
10
2
Order By: Relevance
“…Figure 1 shows that there was a clear polarity reversal in the ipsi-cVEMPs responses between the upper and lower sites in the sterno-mastoid branch of the SCM (CH3 vs. CH5), but not along the cleidomastoid branch of the SCM (CH3 and CH6). This is consistent with results of our previous study (Wei et al 2013). Figure 2 further quantitatively compares the amplitudes of Pk1 and Pk2 from the seven recording sites in the HR and CD conditions (A 350 Hz, B 1000 Hz).…”
Section: Methodssupporting
confidence: 91%
See 4 more Smart Citations
“…Figure 1 shows that there was a clear polarity reversal in the ipsi-cVEMPs responses between the upper and lower sites in the sterno-mastoid branch of the SCM (CH3 vs. CH5), but not along the cleidomastoid branch of the SCM (CH3 and CH6). This is consistent with results of our previous study (Wei et al 2013). Figure 2 further quantitatively compares the amplitudes of Pk1 and Pk2 from the seven recording sites in the HR and CD conditions (A 350 Hz, B 1000 Hz).…”
Section: Methodssupporting
confidence: 91%
“…On the other hand, we have examined whether the SCM is compartmented and has multiple innervation zones (McLoon 1998). We found that the cVEMPs recorded at the sites close to the sterno head exhibit reversed polarity compared to that recorded at the upper sites (Wei et al 2013), which is consistent with the idea of SCM compartmentation. In the current study, we extended our investigation of the SCM-related factors by further testing three specific hypotheses, i.e., the cVEMP response is ipsilateral and dependent on how the SCM tonic level is achieved (e.g., by head rotation or head flexion), and the polarity of the cVEMP response is dependent on the recording site.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations